2015
DOI: 10.1123/jcsp.2015-0006
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Alcohol Abuse Among College Athletes

Abstract: Self-concept theory was used as a theoretical basis to investigate the utility of social norms alcohol prevention programs designed for college athletes. The predictive relationship among alcohol use and athletic identity, competitiveness, drinking game participation, and level of sport participation was investigated. It was discovered that drinking game participation is a significant predictor of total weekly alcohol use above and beyond the other predictors. In addition, drinking game participation and organ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 71 publications
(215 reference statements)
0
3
0
Order By: Relevance
“…The unique schedules and stressors of athletes create divergent motives, age of first consumption, and patterns of alcohol consumption compared to their nonathlete peers (Martens, Dams-O’Connor, & Beck, 2006). Athletic participation has been linked with more frequent consumption, greater drinking quantity, more frequent heavy episodic drinking (HED), and the experience of alcohol-related consequences including alcohol-related injury (Cadigan et al, 2013; Fitzpatrick & Olthuis, 2021; Jones, 2015; Martens, Dams-O’Connor, & Beck, 2006; Mastroleo et al, 2013; Milroy et al, 2014; Parisi et al, 2019; Wetherill & Fromme, 2007; Zhou & Heim, 2014). These findings suggest that those who participate in competitive athletics may be at greater risk for developing AUD, making the collegiate athlete subpopulation a vital target of research within an already at-risk group.…”
mentioning
confidence: 99%
“…The unique schedules and stressors of athletes create divergent motives, age of first consumption, and patterns of alcohol consumption compared to their nonathlete peers (Martens, Dams-O’Connor, & Beck, 2006). Athletic participation has been linked with more frequent consumption, greater drinking quantity, more frequent heavy episodic drinking (HED), and the experience of alcohol-related consequences including alcohol-related injury (Cadigan et al, 2013; Fitzpatrick & Olthuis, 2021; Jones, 2015; Martens, Dams-O’Connor, & Beck, 2006; Mastroleo et al, 2013; Milroy et al, 2014; Parisi et al, 2019; Wetherill & Fromme, 2007; Zhou & Heim, 2014). These findings suggest that those who participate in competitive athletics may be at greater risk for developing AUD, making the collegiate athlete subpopulation a vital target of research within an already at-risk group.…”
mentioning
confidence: 99%
“…A drinking game (DG) is a social drinking activity that requires participants to perform a mental and/or motor task and consists of rules designed to get players drunk (Zamboanga et al, 2013). Participation in DGs can contribute to college students' and student-athletes' risk for heavy alcohol consumption and negative alcohol-related outcomes (Grossbard et al, 2007;Hummer et al, 2011;Jones, 2015;Zamboanga et al, 2008; for reviews, see Kenney et al, 2017;Zamboanga et al, 2014). Although DG participation has been linked to a number of problematic health outcomes (e.g., blackouts, sexual victimization/perpetration; Zamboanga et al, 2014), young adults' awareness of the health hazards associated with heavy drinking does not seem to influence their decision to participate (Polizzotto et al, 2007).…”
Section: Drinking Gamesmentioning
confidence: 99%
“…Furthermore, a number of researchers found that distress is linked to dismal academic performance, absconding as well as low rate of graduation (Wang, 2005). Nonetheless University students suffer from different kinds of stressors during the educational experiences (Ndegwa et al, 2017). Universities are at a higher risk of increased stress (Wanyoike, 2015).…”
Section: Introductionmentioning
confidence: 99%